2019
DOI: 10.1016/j.cub.2019.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Ancient Mitogenomes Reveal the Evolutionary History and Biogeography of Sloths

Abstract: Three subsamples between 187-285 mg were taken from the rib cross section sample of MAPB4R 3965. Subsamples were manually pulverized and washed with 300 µl of 0.5 M EDTA (shaking at 1000 RPM; 20 min; 25°C) to remove dust and surface contaminants.Samples were then subject to alternating rounds of demineralization (0.75 ml of 0.5 M EDTA; shaking at 1000 RPM; ~24 hours; 25°C) and digestion (0.75 ml of ProK Digestion Buffer (0.01M Tris-Cl (pH 9), 0.20 % Sarcosyl, 0.25 mg/ml Proteinase K, 0.01 M CaCl 2 ); rotation;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
2
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 61 publications
4
87
2
4
Order By: Relevance
“…This find has also raised the critical question of a possible link between these Oligocene Puerto Rican chinchilloids and some of the "giant hutias" (Amblyrhiza Cope, 1868 and Elasmodontomys Anthony, 1916), for which a chinchilloid status is also strongly supported in the framework of that study (Marivaux et al, 2020). Although the pre-Pleistocene evolutionary history of these endemic "giant hutias" remains so far undocumented, lineages of these iconic recently-extinct rodents could have a very great antiquity on the islands, extending back more than 30 million years (as also recently demonstrated for West Indian sloths and coquí frogs; Delsuc et al, 2019;Presslee et al, 2019;Blackburn et al, 2020).…”
Section: Introductionsupporting
confidence: 60%
“…This find has also raised the critical question of a possible link between these Oligocene Puerto Rican chinchilloids and some of the "giant hutias" (Amblyrhiza Cope, 1868 and Elasmodontomys Anthony, 1916), for which a chinchilloid status is also strongly supported in the framework of that study (Marivaux et al, 2020). Although the pre-Pleistocene evolutionary history of these endemic "giant hutias" remains so far undocumented, lineages of these iconic recently-extinct rodents could have a very great antiquity on the islands, extending back more than 30 million years (as also recently demonstrated for West Indian sloths and coquí frogs; Delsuc et al, 2019;Presslee et al, 2019;Blackburn et al, 2020).…”
Section: Introductionsupporting
confidence: 60%
“…Lett. 16: 20190947 molecular evidence is consistent with the synchronous arrival of terrestrial organisms to the region approximately 33.9 ± 1 Ma, while others clearly arrived through multiple overwater dispersal events throughout the Neogene or even earlier [8,13,15,35,36,[44][45][46][47][48][49][50]. Furthermore, molecular phylogenetic studies have suggested a similar Oligocene arrival for at least some anuran taxa on the Puerto Rican and Hispaniolan banks, such as Leptodactylus [13] and Peltophryne [15].…”
Section: (C) Descriptionmentioning
confidence: 62%
“…However, these results are preliminary inasmuch as the proposed position of Borikenomys is likely to evolve with additional morphological data. If this phylogenetic link is confirmed, these endemic giant Caribbean rodents could have a remarkable antiquity on the islands (as for Caribbean sloths [27,28] and coquí frogs [75]) and thus could represent a unique case of long-lived insular rodent lineage. Alternatively, these Oligocene Puerto Rican chinchilloids could have become extinct without descendants.…”
Section: Discussionmentioning
confidence: 99%